2015
DOI: 10.1007/s00292-015-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Zervixkarzinome in Mecklenburg-Vorpommern

Abstract: Most cervical cancers and the advanced stages were found in women who did not participate in the screening program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Cancer stage at diagnosis is a critical determinant of cancer outcomes and is directly associated with survival in cancer patients 10 . Previous studies showed that women rarely or never screened were more likely to be diagnosed at late stage than women undergoing routine screenings 1115 . Our study showed that patients were more likely to be diagnosed at an early stage with more frequent screening.…”
Section: Discussionmentioning
confidence: 98%
“…Cancer stage at diagnosis is a critical determinant of cancer outcomes and is directly associated with survival in cancer patients 10 . Previous studies showed that women rarely or never screened were more likely to be diagnosed at late stage than women undergoing routine screenings 1115 . Our study showed that patients were more likely to be diagnosed at an early stage with more frequent screening.…”
Section: Discussionmentioning
confidence: 98%
“…In Germany, a case study conducted in Mecklenburg-Western Pomerania retrospectively investigated CCS participation preceding a cervical cancer diagnosis. Fifty-eight per cent of women with cervical cancer had no Pap smear taken in the five years prior to diagnosis, whilst the remaining 42% had at least one Pap smear recorded in this period [9]. These findings were based on cytological laboratories records reported to the Quality Assurance Commission of the Medical Association in Mecklenburg-Western Pomerania.…”
Section: Plos Onementioning
confidence: 99%
“…The estimated triennial participation rate ranges from 75% to 85% [6][7][8]. Data on the association between CCS participation and cervical cancer in Germany are limited to case series and reports but indicate that participation in CCS has been low among women who developed this malignancy [9]. Therefore, the present study aimed to investigate the impact of opportunistic CCS on cervical cancer, adjusting for known and potential risk factors including socio-demographic characteristics, smoking, oral contraceptive (OC) use, parity, body mass index (BMI), and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Mit diesem Konzept und den Abklärungsmodalitäten bei auffälliger Zytologie konnte die Inzidenz des Zervixkarzinoms um mehr als 70 % gesenkt werden [10,26]. Bei der Restinzidenz des Zervixkarzinoms unter Screening-Teilnehmerinnen handelt es sich überwiegend um prognostisch günstige Karzinome [4,19].…”
Section: Statistische Auswertungunclassified